The Effects of Acute Ammonia Exposure on the Immune Response of Juvenile Freshwater Prawn, Macrobrachium Nipponense. Issue 1 (1st January 2015) - Zhang, Wenyi; Jiang, Qichen; Liu, Xiaoqian; Pan, Dongmei; Yang, Yuanhao; Yang, Jiaxin
Abstract: The effects of acute ammonia exposure on juvenile Macrobrachium nipponense (De Haan, 1849) were evaluated. The LC_50 values and 95% confident intervals for total ammonia nitrogen (TAN) after 24, 48, 72 and 96 hours' exposure were 139.78 (108.77-179.63), 84.17 (50.40-127.87), 64.07 (44.78-91.66) and 40.42 (30.46-53.62) mg/l . Then a 96-hour acute toxicity experiment was conducted in five concentrations of TAN (0, 5, 10, 15 and 20 mg/l ). The whole-body activities of alkaline phosphatase (AKP), acid phosphatase (ACP), superoxide dismutase (SOD), catalase (CAT), and the concentration of malonaldehyde (MDA) were measured. The results demonstrate that the concentrations used in this study induce the immune response and that damage may be accompanied by a depression of the antioxidant defense system and the accumulation of malonaldehyde (MDA). These results suggest that changes in whole-body immune parameters of juvenile prawns are effective to characterize overall prawn health and environmental conditions.